Accrual versus Cash-Basis Accounting Methods: An Agency-Theoretic Comparison - KWON, Young Koan (Institutional Knowledge at Singapore Management University, 1989)
In an agency setting with moral hazard, this paper analytically demonstrates that accrual accounting is superior to cash-basis accounting (subject to costs). The main reason is that accrual accounting information more fully reflects the overall effects of managerial actions or efforts on future cash flows than cash flow realizations in any given period. As a result, accrual accounting information is more efficient than cash-basis accounting information for both motivating managers to expend efforts and sharing risks under moral hazard.